Versatile strategy for isolating transcription activator‐like effector nuclease‐mediated knockout mutants in Caenorhabditis elegans. (17th December 2013) - Sugi, Takuma; Sakuma, Tetsushi; Ohtani, Yasuko; Yamamoto, Takashi
<x xml:space="preserve">Abstract</x> Targeted genome editing using transcription activator‐like effector nuclease (TALEN) and clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 systems has recently emerged as a potentially powerful method for creating locus‐specific mutations in Caenorhabditis elegans. Due to the low mutation frequencies, one of the crucial steps in using these technologies is screening animals that harbor a targeted mutation. In previous studies, identifying targeted mutations in C. elegans usually depended on observations of fluorescent markers such as a green fluorescent protein or visible phenotypes such as dumpy and uncoordinated phenotypes. However, this strategy is limited in practice because the phenotypes caused by targeted mutations such as defects in sensory behaviors are often apparently invisible. Here, we describe a versatile strategy for isolating C. elegans knockout mutants by TALEN‐mediated genome editing and a heteroduplex mobility assay. We applied TALENs to engineer the locus of the neural gene glr‐1, which is a C. elegans AMPA‐type receptor orthologue that is known to have crucial roles in various sensory behaviors. Knockout mutations in the glr‐1 locus, which caused defective mechanosensory behaviors, were efficiently identified by the heteroduplex mobility assay. Thus, we demonstrated the utility of a TALEN‐based knockout strategy for creating C. elegans with mutations that cause invisible phenotypes.